2012
DOI: 10.1371/journal.pone.0028931
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling Using Genome-Wide Significant Coronary Artery Disease Risk Variants Does Not Improve the Prediction of Subclinical Atherosclerosis: The Cardiovascular Risk in Young Finns Study, the Bogalusa Heart Study and the Health 2000 Survey – A Meta-Analysis of Three Independent Studies

Abstract: BackgroundGenome-wide association studies (GWASs) have identified a large number of variants (SNPs) associating with an increased risk of coronary artery disease (CAD). Recently, the CARDIoGRAM consortium published a GWAS based on the largest study population so far. They successfully replicated twelve already known associations and discovered thirteen new SNPs associating with CAD. We examined whether the genetic profiling of these variants improves prediction of subclinical atherosclerosis – i.e., carotid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…10 Genetic markers have also not been shown to improve prediction of subclinical atherosclerosis beyond traditional risk factors. 11 …”
Section: Family History and Geneticsmentioning
confidence: 99%
“…10 Genetic markers have also not been shown to improve prediction of subclinical atherosclerosis beyond traditional risk factors. 11 …”
Section: Family History and Geneticsmentioning
confidence: 99%
“…They also analyzed the association of the individual SNPs with the subclinical atherosclerosis measurements; although 2 SNPs tended to associate with carotid IMT (rs4977574) or carotid elasticity (rs4773144), these findings could not be replicated. 36 Finally, Zhang et al 28 selected 10 SNPs associated with CAD (only rs1333049 in common with our study) and analyzed their association with 4 subclinical atherosclerosis measurements (IMTcca and MTica, presence of carotid plaque, and pathologic ABI) in 5 community-based surveys. They found that the rs780094 (GCKR) was associated with carotid plaque in the American Indian population but not in European American, African American, or Mexican American populations.…”
Section: Discussionmentioning
confidence: 96%
“…Conde et al 35 used data from 3 European communitybased studies to assess the association between 12 genetic variants (7 of them included in our study, which added the LPA SNP and the ALOX5AP HapB) and mean common carotid artery IMT; none of the individual variants was associated with the outcome of interest. Hernesniemi et al 36 analyzed the association between a genetic risk score, based on 24 SNPs identified in GWAS as associated with CAD (7 of them included in our study), and carotid IMT and carotid elasticity in 2 Finnish populations and an American population. They found no association with carotid IMT measured at 2 different times (2001 and 2007) or with the progression of the thickness in this 6-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many attempts to assess various configurations from the single genetic risk variant 9p21 112 to combinations of ≤13 variants. [113][114][115][116][117] All of these studies show a good correlation between the genetic risk variants and the risk of CAD with some improvement in the prediction of CAD. However, the conventional criteria for significant improvement is judged on whether it changes the net reclassification index or improves discrimination by the conventional ethics, referred to as C-index.…”
Section: Clinical Application Of Genetic Risk Variants For the Prevenmentioning
confidence: 94%